Computational thinking education: Issues and challenges - Angeli, Charoula; Giannakos, Michail (Computers in human behavior, 2020)
Computational Thinking is a term applied to describe the increasing attention on students' knowledge development about designing computational solutions to problems, algorithmic thinking, and coding. It focuses on skills children develop from practicing programming and algorithms, and enables the development of qualities such as abstract thinking, problem solving, pattern recognition, and logical reasoning. Contemporary educational and infrastructural developments, like “CS for All” (https://www.csforall.org/), ISTE's Standards for Students in Computational Thinking (https://www.iste.org/explore/Solutions/Computational-thinking-for-all?articleid=152), Computer Science Teachers Association's Concepts of Computational Thinking (http://advocate.csteachers.org/2014/09/15/computational-thinking-and-beyond/), and the appearance of tools such as robotics, 3D printing, microprocessors, and intuitive programming languages posit Computational Thinking as a very promising area to support these learning competences. In this special issue of Computers in Human Behavior, the Editors report four studies conducted by interdisciplinary teams. The introduction to the special issue also draws attention to the great potential and need for further research in the area of Computational Thinking Education to engage students in meaningful learning so as to develop useful thinking skills and digital competences. Finally, the Editorspropose directions for future research and practice in Computational Thinking Education.